On relation between algebraic and ordinary differential algebraic invariants of motion groups - Bekbaev, Ural (Pleiades Publishing, Ltd., 2014)
As applied to differential geometry it provides a method to describe differential algebraic $H$-invariants of paths by the use of algebraic $H$-invariants, where $H$ is any subgroup of the affine group. It is shown also that a generating system of differential $H$-invariants of curves can be derived from given system of differential $H$-invariants of paths. All relations among members of the obtained generating system can be predicted as well.